Effects of repetitive transcranial magnetic stimulation at different targets on brain function in stroke patients: a randomized controlled trial - Zhao, Li; Chen, Li; Wang, Chunyan; Li, Sha; Wan, Chunxiao (Frontiers in Neurology, 2024)
Introduction Repetitive transcranial magnetic stimulation (rTMS) can improve post stroke motor function. However, there is little research on targets. The purpose of this study is to investigate the effects of rTMS therapy with different targets on post stroke motor function and neural plasticity. Methods Fifty-four subjects were randomly divided into M1 (Primary motor area) group, SMA (supplementary motor area) group and Sham group, and were given 10 Hz on the affected M1 area, SMA area and sham stimulation rTMS. The primary outcomes included Fugl-Meyer Assessment Upper Extremity Scale (FMA-UE), Fugl-Meyer Assessment Lower Extremity Scale (FMA-LE) and Berg balance scale (BBS). Secondary outcomes: amplitude of low frequency fluctuation (ALFF), regional homogeneity (ReHo) and functional connectivity (FC) were analyzed by functional magnetic resonance imaging (fMRI) to evaluate brain functional activation and functional connectivity changes. Results The 2-way repeated-measures ANOVA revealed a significant group × time interaction (F = 23.494, p < 0.001; F = 10.801, p < 0.001; F = 17.812, p < 0.001) in the FMA-UE, FMA-LE and BBS scores. Post hoc analysis indicated that 4 weeks of SMA rTMS resulted in an increase in FMA-UE, FMA-LE and BBS scores compared with Sham group (p = 0.006; p = 0.033; p = 0.012), SMA group was significantly increased in BBS compared with M1 group (p = 0.034). Moreover, there were significant effects of time in all 3 groups in the FMA-UE, FMA-LE and BBS scores (p < 0.001). In addition, the increase of ALFF in the supramarginal gyrus on the affected side was correlated with better FMA-UE recovery, the increase of ALFF in the middle temporal gyrus and the middle frontal gyrus on the affected side was positively correlated with the improvement of BBS, and the ALFF in the cerebellum on the healthy side was negatively correlated with the improvement of BBS. There was a positive correlation between FC (SMA – ipsilateral cerebellum) changes and BBS changes in SMA group. Discussion In conclusion, SMA-rTMS intervention has a better recovery effect on motor dysfunction after stroke than Sham-rTMS. SMA-rTMS led to similar improvement on motor function but significantly greater improvement on balance compared to M1-rTMS, and this may pave a new way for stroke rehabilitation. Clinical trial registration Registration number: ChiCTR2200060955, https://www.chictr.org.cn/.